2018
DOI: 10.1016/j.devcel.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Transcriptomics of C. elegans Males and Hermaphrodites Identifies Sex-Specific Differences in Gene Expression Patterns

Abstract: Highlights d 20 mm resolution AP gene expression maps of C. elegans males and hermaphrodites d Resource for in silico identification of cell-and tissuespecific genes d Identification of sex-specific germline and sperm genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 52 publications
8
87
0
Order By: Relevance
“…The transcriptome analysis of distinct cell lineages, as conducted for C. elegans precursors of endoderm, mesoderm and ectoderm (Hashimshony et al 2014) or for single-cell transcriptomes throughout embryogenesis (Hashimshony et al 2012, Tintori et al 2016, Packer et al 2019, provides one intriguing scheme for approaching this issue. Another approach could incorporate developmental time into transcriptome analysis of serial-sectioned samples to access 4-dimensional expression profiles through developmental space and time (Ebbing et al 2018).…”
Section: Modularity Of Genetic Network Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptome analysis of distinct cell lineages, as conducted for C. elegans precursors of endoderm, mesoderm and ectoderm (Hashimshony et al 2014) or for single-cell transcriptomes throughout embryogenesis (Hashimshony et al 2012, Tintori et al 2016, Packer et al 2019, provides one intriguing scheme for approaching this issue. Another approach could incorporate developmental time into transcriptome analysis of serial-sectioned samples to access 4-dimensional expression profiles through developmental space and time (Ebbing et al 2018).…”
Section: Modularity Of Genetic Network Architecturementioning
confidence: 99%
“…Genes also can be grouped according to patterns of co-expression to analyze for consistent differences in rates of molecular evolution among them or among parameters of mathematical functions that describe the temporal profiles of expression (Coronado-Zamora et al 2019, Cutter et al 2019. Spatial definition of expression can enhance such approaches using tissue-and sex-specificity (Kim et al 2016), restricted cell-lineages (Hashimshony et al 2014), or tomographic expression profiling (Ebbing et al 2018). While mRNA expression is most commonly accessed, all of these approaches can be extended to protein expression; protein levels appear to differ less between species than do transcriptomes (Leducq et al 2012, Khan et al 2013.…”
Section: Concentricmentioning
confidence: 99%
“…Because Orsay virus infection does not infect all individuals within the population and its cellular tropism is limited to the intestinal cells [7,8], we cannot rule out there may be local changes in transcription in the intestinal cells or for certain individuals of CB4856. Transcriptional techniques, such as single-cell RNA-seq or TOMO-seq [48,49], that identify gene expression within infected cells could provide more details about the transcriptional response in the cells at stake.…”
Section: Transcriptional Activation Of the Ipr In Two Genetically DIVmentioning
confidence: 99%
“…C. elegans possess only one population of stem cells-the germlinewhich originate from a single cell and become progressively more mature as they migrate through the gonad away from the distal tip cell (Kimble, 1981). In fact, previous studies have found mafr-1 enriched in the C. elegans germline, but the significance of this finding has never been studied (Ebbing et al, 2018;Grun et al, 2014;Han et al, 2017).…”
Section: Discussionmentioning
confidence: 99%